(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
Owing to rapidly changing environmental conditions it becomes more difficult to create competent policy of business. Valid creation of the development strategy of the enterprise allows the company not only to stay afloat, but also to go promptly forward, gradually winning the increasing share of the market. Questions connected with a research of the market and formation on the basis of this analysis of the development strategy of trade and industrial enterprise are considered in the article.